Professor Emeritus Dato’ Seri Ir Dr Zaini Ujang shares sustainability practices and global academic world - Nur Hartini, Mohd Hatta (UMPSA, 2025)
GAMBANG, 27 November 2025 – Academic figure and recipient of the National Engineering Icon Award 2025, Professor Emeritus Dato’ Seri Ir Dr Zaini Ujang, met the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) community today in the 100 Days World Lecture Tour Sharing Session held in conjunction with the UMPSA Academic Advising System Empowerment Workshop.